Meeting with triumph and disaster: Osimertinib in T790M-unknown CNS progression in EGFR-mutated non-small cell lung cancer. Issue 6 (December 2018) - Facchinetti, Francesco; Bozzetti, Francesca; Minari, Roberta; Ceccon, Giovanni; Zielli, Teresa; Florindo, Irene; Crisi, Girolamo; Tiseo, Marcello
Introduction: Treatment paradigms for EGFR -mutated non-small cell lung cancer (NSCLC) have successfully evolved since the introduction of osimertinib. The detection of EGFR T790M mutation in plasma or tumor samples obtained at disease progression to first-/second-generation EGFR inhibitors is mandatory for osimertinib prescription. Nevertheless, pharmacokinetics properties of osimertinib guarantee its usefulness in central nervous system (CNS) disease even in the case of T790M-negative or unknown status. Patients and methods: In this brief report, we share the clinical histories of two patients with CNS-preeminent progression under first-/second-generation EGFR inhibitors in which it was not possible to document the presence of T790M resistance mutation. Results: Patient outcomes diverged dramatically due to the differential availability of off-label osimertinib. Conclusions: Waiting for the novel molecule to be approved and licensed in first-line treatment, our report of hope and frustration is intended to stress the opportunity of its administration in the case of CNS failure of first-line EGFR inhibition, even in the absence of T790M proof.